High-purity ultralow-oxygen-content ruthenium-tantalum alloy target material and preparation method thereof
Through low-pressure pre-pressure, vacuum calcination and thermal isostatic sintering, the problems of high oxygen content and poor density of RuTa alloy targets were solved, and high-purity ultra-low oxygen content RuTa alloy targets were prepared, which improved the diffusion barrier layer. Performance extends the service life of integrated circuits.
Patent Information
- Application Number
- CN202411352215.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
AI Technical Summary
The existing RuTa alloy target preparation methods have problems with high oxygen content and poor density, which leads to poor performance of the diffusion barrier film and affects the service life of the integrated circuit.
The combination of low-pressure prepression and high vacuum calcination is adopted to perform ball milling through argon-protected and ruthenium-based mixture balls and mixing tanks, followed by hot isostatic sintering, and sintering in graphite molds to reduce oxygen content and Impurities are introduced to improve the purity and density of the alloy.
The high-purity ultra-low oxygen content RuTa alloy target was successfully prepared, which reduced the resistance of the film, improved the barrier effect of the diffusion barrier layer, and enhanced the application performance in integrated circuits.
Smart Images

Figure CN119282115A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetron sputtering alloy target materials, and relates to a high-purity ultra-low oxygen content ruthenium-tantalum alloy target material and a preparation method thereof. Background Art
[0002] With the large-scale development of integrated circuit technology, copper materials with better thermal stability, lower resistivity and better resistance to electromigration have replaced aluminum as a new generation of wiring interconnection materials. However, copper materials are prone to interdiffusion with substrate silicon and low-potassium dielectrics, forming a strong trap effect on carriers in microelectronic semiconductor devices, which can easily cause integrated circuits to fail prematurely. In order to increase the service life of electronic components, it is necessary to add a diffusion barrier layer between the copper film and the substrate silicon wafer and low-potassium dielectric to prevent their diffusion. As a better diffusion barrier material, RuTa alloy target material is increasingly important and in demand in the integrated circuit industry.
[0003] The purity of RuTa alloy target affects the performance of diffusion barrier film. When the impurities and oxygen content in the target increase, the film performance will deteriorate. Among them, the increase of oxygen and carbon content will lead to the aggregation of particles in the film and cause the resistance to increase. The RuTa alloy target has low purity and high oxygen content, and its barrier effect is poor. Potassium and sodium are fast-diffusion metals, and their diffusion easily leads to the deterioration of the interface characteristics of semiconductor integrated circuits. Uranium and thorium are radioactive elements, and their diffusion will excite electron holes and affect integrated circuits. The diffusion of iron and other elements will cause interface leakage and increase resistance. Therefore, improving the purity of RuTa alloy target and reducing its oxygen content are of great significance to improve the performance of diffusion barrier film and enable the diffusion barrier film to be better used in integrated circuits.
[0004] At present, the preparation methods of RuTa alloy targets usually include smelting and casting, powder metallurgy, etc. Among them, the smelting and casting method is usually a combination of smelting + heat treatment. The smelting temperature is above 3000℃, which has high energy consumption and high cost. Moreover, the components of the furnace chamber accessories are more likely to volatilize and enter the target material under ultra-high temperature, causing target material pollution. At the same time, the target material has coarse grains after smelting and requires subsequent heat treatment. The production process is multi-step and the cycle is long. The most commonly used powder metallurgy method is vacuum hot pressing. Although its process is simpler than the smelting + heat treatment method, the RuTa alloy target prepared by it still has problems such as high oxygen content and poor density.
[0005] Therefore, it is necessary to provide a high-purity and ultra-low oxygen content ruthenium-tantalum alloy target and a preparation method thereof, so as to obtain a ruthenium-tantalum alloy target with higher purity and lower oxygen content, thereby improving the performance of the diffusion barrier layer film. Summary of the invention
[0006] In order to overcome the problems in the background technology, the present invention prepares a ruthenium-tantalum alloy target with high purity and low oxygen content, reduces the resistance of the diffusion barrier film itself, improves the film barrier effect, and thus improves the application effect of the diffusion barrier layer in integrated circuits.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a high-purity ultra-low oxygen content ruthenium-tantalum alloy target, the preparation method comprising the following steps:
[0009] (1) Powder mixing: Under the protection of argon gas, tantalum hydride powder and ruthenium powder are mixed evenly to obtain a mixed powder;
[0010] (2) low-pressure pre-pressing: the mixed powder in step (1) is placed in a graphite mold lined with ruthenium foil, and low-pressure pre-pressed to obtain a preform;
[0011] (3) high vacuum calcination: vacuum calcining the preform obtained in step (2) to obtain a calcined blank;
[0012] (4) hot isostatic pressing and sintering: hot isostatic pressing and sintering the calcined blank obtained in step (3) to obtain a sintered blank;
[0013] (5) Grinding and polishing: The sintered blank obtained in the step (4) is subjected to mechanical grinding and polishing until the surface roughness of the sintered blank Ra is less than or equal to 1.6 μm, thereby obtaining a high-purity and ultra-low oxygen content ruthenium-tantalum alloy target material for magnetron sputtering.
[0014] Preferably, the purity of the ruthenium powder and the tantalum hydride powder in step (1) is ≥99.995%, and the particle size is 50-100 μm.
[0015] Preferably, in step (1), a three-dimensional vibration ball mill is used to evenly mix the tantalum hydride powder and the ruthenium powder. During the mixing process, the ball-to-material ratio is 5 to 10:1, the powder mixing frequency is 15 to 25 Hz, and the powder mixing time is 12 to 24 hours.
[0016] Preferably, the mixing balls and the mixing tank of the three-dimensional vibration ball mill are made of ruthenium metal.
[0017] Preferably, the thickness of the ruthenium foil lined in the graphite mold is 1 to 2 mm.
[0018] Preferably, in step (2), the low-pressure pre-pressing pressure is 5 to 10 MPa, and the holding time is 1 to 2 hours.
[0019] Preferably, the vacuum calcination temperature in step (3) is 900-1100°C, the calcination time is 6-12h, and the vacuum degree is 10 -3~10 -4 Pa.
[0020] Preferably, in step (4), the hot isostatic pressing sintering temperature is 1200-1450° C., the sintering time is 1-4 hours, and the pressure is 30-50 MPa.
[0021] On the other hand, the present invention provides a high-purity ultra-low oxygen content ruthenium-tantalum alloy target prepared by the above preparation method, wherein the high-purity ultra-low oxygen content ruthenium-tantalum alloy target has an oxygen content of ≤20ppm and a purity of ≥99.995%.
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention performs low-pressure pre-pressing and high-vacuum calcination to make the decomposition and reduction of tantalum hydride more thorough, effectively reduce the impurities and oxygen content in the alloy target, and effectively improve the purity of the alloy target.
[0024] 2. The present invention uses tantalum hydride as a raw material for preparing the alloy target, and utilizes the characteristic of tantalum hydride that it is not easily oxidized to effectively reduce the introduction of oxygen, thereby further reducing the oxygen content in the ruthenium-tantalum alloy target.
[0025] 3. The present invention uses ruthenium mixing balls and mixing tanks for mixing, thereby reducing the amount of impurities introduced during the ball milling process, which helps to improve the purity of the final alloy target material.
[0026] 4. The present invention compensates for the influence of high vacuum calcination on the density of the alloy by hot isostatic pressing sintering, realizes the densification of the ruthenium-tantalum alloy target, and avoids the low density of the alloy affecting its performance.
[0027] 5. In the present invention, the blank is not removed from the graphite mold during the vacuum calcination and hot isostatic pressing sintering stages. By using a graphite mold lined with ruthenium foil, the carbon in the mold is prevented from diffusing into the RuTa alloy during the sintering process, which helps to improve the purity of the alloy target. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the fracture surface of the high-purity and ultra-low oxygen content ruthenium-tantalum alloy target of the present invention.
[0029] Figure 2 This is a scanning electron microscope image of the fracture surface of the high-purity and ultra-low oxygen content ruthenium-tantalum alloy target of the present invention (scale bar 10 μm). DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments.
[0031] In the examples of the present invention, all chemical reagents not specified were used in the experiments with analytically pure reagents.
[0032] Example 1
[0033] In this embodiment, a ruthenium-tantalum alloy target is prepared by the following method:
[0034] (1) Powder mixing: Use ruthenium powder and tantalum hydride powder with a particle size of 20 to 50 μm and a purity of ≥99.995% as raw materials. In a glove box with argon as a protective atmosphere, weigh ruthenium powder and tantalum hydride powder (the weighing amounts of ruthenium powder and tantalum hydride powder can be determined according to the conventional ruthenium tantalum alloy target material formula), then put the weighed ruthenium powder and tantalum hydride powder into a ball mill and fill the ball mill with argon as a protective atmosphere. The ball-to-material ratio is 5:1. The mixing balls and mixing tank are made of ruthenium. A three-dimensional vibration ball mill is used for powder mixing. The mixing frequency is 25 Hz and the mixing time is 18 hours to obtain a uniform ruthenium-tantalum hydride mixed powder.
[0035] (2) Low-pressure pre-pressing: The uniformly mixed ruthenium-tantalum hydride mixed powder is loaded into a high-strength graphite mold lined with ruthenium foil. The mixed powder and the high-strength graphite mold are separated by ruthenium foil with a thickness of 1 mm. Low-pressure pre-pressing is performed by a hydraulic press at a pressure of 5 MPa and a holding time of 2 hours to obtain a preform pre-pressed at low pressure. The pre-pressing pressure is small, and no metallurgical bonding occurs inside the mixed powder. The structural properties of the mixed powder itself are almost unchanged. The dispersed mixed powder is only compacted to form a block with a specific structure.
[0036] (3) High vacuum calcination: After low pressure pre-pressing, the ruthenium foil-lined graphite mold containing the preform is placed in a high vacuum sintering furnace, the upper pressure head of the mold is removed, and the vacuum is evacuated to 10 -3 ~10 -4 Pa, and then vacuum calcined at a temperature of 1000°C for 8 h to obtain a RuTa alloy calcined billet.
[0037] (4) Hot isostatic pressing sintering: The calcined blank after high vacuum calcination is placed in a hot isostatic pressing sintering furnace, slowly pressurized to 40 MPa, and sintered at a heating rate of 50 °C / min to 1200 °C. The sintering time is 4 h.
[0038] (5) Grinding and polishing: The RuTa alloy ingot obtained by hot isostatic pressing and sintering is mechanically ground and polished to obtain a high-purity and ultra-low oxygen content RuTa alloy target for magnetron sputtering.
[0039] The contents of various impurities in the RuTa alloy target prepared in this embodiment were detected, and the results are shown in Table 1. The density of the RuTa alloy target prepared in this embodiment was detected, and the results are shown in Table 2.
[0040] Example 2
[0041] In this embodiment, a ruthenium-tantalum alloy target is prepared by the following method:
[0042] (1) Powder mixing: Use ruthenium powder and tantalum hydride powder with a particle size of 50 to 100 μm and a purity of ≥99.995% as raw materials. In a glove box with argon as a protective atmosphere, weigh the ruthenium powder and tantalum hydride powder (the weighing amounts of ruthenium powder and tantalum hydride powder can be determined according to the conventional ruthenium tantalum alloy target material formula), then put the weighed ruthenium powder and tantalum hydride powder into a ball mill and fill the ball mill with argon as a protective atmosphere. The ball-to-material ratio is 10:1. The mixing balls and mixing tank are made of ruthenium. A three-dimensional mixer is used for powder mixing. The mixing frequency is 15 Hz and the mixing time is 12 h to obtain a uniform ruthenium-tantalum hydride mixed powder.
[0043] (2) Low-pressure pre-pressing: The uniformly mixed ruthenium-tantalum hydride mixed powder is loaded into a high-strength graphite mold lined with ruthenium foil. The mixed powder and the high-strength graphite mold are separated by ruthenium foil with a thickness of 2 mm. Low-pressure pre-pressing is performed by a hydraulic press with a pressure of 10 MPa and a holding time of 1 h to obtain low-pressure pre-pressed ruthenium-tantalum hydride mixed powder.
[0044] (3) High vacuum calcination: put the mixed powder and graphite mold after low pressure pre-pressing into a high vacuum sintering furnace, remove the mold upper pressure head, and evacuate to 10 -3 ~10 -4 Pa, and then vacuum calcined at a temperature of 1100°C for 6 h to obtain a RuTa alloy calcined billet.
[0045] (4) Hot isostatic pressing sintering: The calcined blank after high vacuum calcination is placed in a hot isostatic pressing sintering furnace, slowly pressurized to 30 MPa, and sintered at a heating rate of 80 °C / min to 1350 °C for 3 h.
[0046] (5) Grinding and polishing: The RuTa alloy ingot obtained by hot isostatic pressing and sintering is mechanically ground and polished to obtain a high-purity and ultra-low oxygen content RuTa alloy target for magnetron sputtering.
[0047] The contents of various impurities in the RuTa alloy target prepared in this embodiment were detected, and the results are shown in Table 1. The density of the RuTa alloy target prepared in this embodiment was detected, and the results are shown in Table 2.
[0048] Example 3
[0049] In this embodiment, a ruthenium-tantalum alloy target is prepared by the following method:
[0050] (1) Powder mixing: Use ruthenium powder and tantalum hydride powder with a particle size of 20 to 50 μm and a purity of ≥99.995% as raw materials. In a glove box with argon as a protective atmosphere, weigh ruthenium powder and tantalum hydride powder (the weighing amounts of ruthenium powder and tantalum hydride powder can be determined according to the conventional ruthenium tantalum alloy target material formula), then put the weighed ruthenium powder and tantalum hydride powder into a ball mill and fill the ball mill with argon as a protective atmosphere. The ball-to-material ratio is 8:1. The mixing balls and mixing tank are made of ruthenium. A three-dimensional mixer is used for powder mixing. The mixing frequency is 20 Hz and the mixing time is 24 hours to obtain a uniform ruthenium-tantalum hydride mixed powder.
[0051] (2) Low-pressure pre-pressing: The uniformly mixed ruthenium-tantalum hydride mixed powder is loaded into a high-strength graphite mold lined with ruthenium foil. The mixed powder and the high-strength graphite mold are separated by ruthenium foil with a thickness of 1.5 mm. Low-pressure pre-pressing is performed by a hydraulic press with a pressure of 8 MPa and a holding time of 1.5 h to obtain a low-pressure pre-pressed ruthenium-tantalum hydride mixed powder.
[0052] (3) High vacuum calcination: put the mixed powder and graphite mold after low pressure pre-pressing into a high vacuum sintering furnace, remove the mold upper pressure head, and evacuate to 10 -3 ~10 -4 Pa, and then vacuum calcined at 900 ° C for 12 h to obtain a RuTa alloy calcined billet.
[0053] (4) Hot isostatic pressing sintering: The calcined blank after high vacuum calcination is placed in a hot isostatic pressing sintering furnace, slowly pressurized to 50 MPa, and sintered at a heating rate of 100 °C / min to 1450 °C for 1 h.
[0054] (5) Grinding and polishing: The RuTa alloy ingot obtained by hot isostatic pressing and sintering is mechanically ground and polished to obtain a high-purity and ultra-low oxygen content RuTa alloy target for magnetron sputtering.
[0055] The contents of various impurities in the RuTa alloy target prepared in this embodiment were detected, and the results are shown in Table 1. The density of the RuTa alloy target prepared in this embodiment was detected, and the results are shown in Table 2.
[0056] Table 1
[0057]
[0058]
[0059] It can be seen from Table 1 that in Example 1 of the present invention, the total content of all impurities is only 25.76ppm (according to the general rule, the calculation of the impurity content of the target does not include the content of gas impurities such as oxygen and carbon), that is, the purity of the ruthenium-tantalum alloy target prepared in Example 1 is 99.997424%; in Example 2 of the present invention, the total content of all impurities is only 33.66ppm, that is, the purity of the ruthenium-tantalum alloy target prepared in Example 2 is 99.996634%; in Example 3 of the present invention, the total content of all impurities is only 34.04ppm, that is, the purity of the ruthenium-tantalum alloy target prepared in Example 3 is 99.996596%. In addition, in Examples 1-3, the oxygen content does not exceed 20ppm, and the carbon content does not exceed 15ppm. The ruthenium-tantalum alloy target prepared by the present invention not only has a low oxygen content, but also has a low carbon content.
[0060] Table 2
[0061] Example 1 Example 2 Example 3 Density 99.20% 99.31% 99.13%
[0062] It can be seen from Table 2 that the ruthenium-tantalum alloy target prepared by the present invention not only has high purity and low impurity content, but also has a high density.
[0063] pass Figure 1 It can be seen that the grain size of the ruthenium-tantalum alloy target prepared by the present invention is relatively small.
[0064] In the process of preparing the ruthenium-tantalum alloy target material of the present invention, after low pressure and pressing, the ruthenium powder and the tantalum hydride powder are in a mechanically bonded state, which is conducive to promoting the more thorough decomposition of the tantalum hydride during the vacuum calcination process, and is also conducive to promoting the full reduction of the hydrogen generated after the decomposition of the tantalum hydride, and effectively improving the effect of reducing the oxygen content. At the same time, compared with the dispersed and disordered state of the mixed powder, the preform has a more concentrated specific structure, which can reduce its contact area with the air, thereby reducing the pollution of the air to the preform.
[0065] During the vacuum calcination stage, the decomposition of tantalum hydride will produce voids, resulting in a decrease in density. Therefore, hot isostatic pressing sintering is used to compensate for the impact of vacuum calcination on the final prepared alloy target material, so that the final alloy target material maintains good comprehensive performance and meets the requirements for the use of the alloy target material.
Claims
1. A method for preparing a high-purity ultra-low oxygen content ruthenium-tantalum alloy target, characterized in that: The preparation method comprises the following steps: (1) Powder mixing: Under the protection of argon gas, tantalum hydride powder and ruthenium powder are mixed evenly to obtain a mixed powder; (2) low-pressure pre-pressing: the mixed powder in step (1) is placed in a graphite mold lined with ruthenium foil, and low-pressure pre-pressed to obtain a preform; (3) high vacuum calcination: vacuum calcining the preform obtained in step (2) to obtain a calcined blank; (4) hot isostatic pressing and sintering: hot isostatic pressing and sintering the calcined blank obtained in step (3) to obtain a sintered blank; (5) Grinding and polishing: The sintered blank obtained in the step (4) is subjected to mechanical grinding and polishing until the surface roughness of the sintered blank Ra is less than or equal to 1.6 μm, thereby obtaining a high-purity and ultra-low oxygen content ruthenium-tantalum alloy target material for magnetron sputtering.
2. The preparation method according to claim 1, characterized in that: The purity of the ruthenium powder and the tantalum hydride powder in step (1) is ≥99.995%, and the particle size is 50-100 μm.
3. The preparation method according to claim 1, characterized in that: In the step (1), a three-dimensional vibration ball mill is used to evenly mix the tantalum hydride powder and the ruthenium powder. During the mixing process, the ball-to-material ratio is 5 to 10:1, the powder mixing frequency is 15 to 25 Hz, and the powder mixing time is 12 to 24 hours.
4. The preparation method according to claim 3, characterized in that: The mixing balls and the mixing tank of the three-dimensional vibration ball mill are both made of ruthenium metal.
5. The preparation method according to claim 1, characterized in that: The thickness of the ruthenium foil lined in the graphite mold is 1 to 2 mm.
6. The preparation method according to claim 1, characterized in that: In the step (2), the pressure of the low-pressure pre-pressing is 5 to 10 MPa, and the holding time is 1 to 2 hours.
7. The preparation method according to claim 1, characterized in that: The vacuum calcination temperature in step (3) is 900-1100° C., the calcination time is 6-12 hours, and the vacuum degree is 10 -3 ~10 -4 Pa.
8. The preparation method according to claim 1, characterized in that: In the step (4), the hot isostatic pressing sintering temperature is 1200-1450° C., the sintering time is 1-4 hours, and the pressure is 30-50 MPa.
9. The high-purity ultra-low oxygen content ruthenium-tantalum alloy target prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The high-purity ultra-low oxygen content ruthenium-tantalum alloy target material has an oxygen content of ≤20ppm and a purity of ≥99.995%.